A novel orally active gonadotropin‐releasing hormone antagonist, relugolix, is a potential substitute for injectable GnRH antagonists in controlled ovarian stimulation in assisted reproductive technology - Michiko Hamada; Michiharu Horikawa; Chie Ensaka; Megumi Enomoto; Rena Ishii; Rena Toriumi; Naoyuki Tachibana; Yuji Taketani (Reproductive Medicine and Biology, 2022)
Abstract Purpose To evaluate the efficacy of an oral gonadotropin‐releasing hormone antagonist (GnRH Ant), relugolix (R), for assisted reproductive technology (ART). Methods We enrolled women undergoing ART using a GnRH Ant for controlled ovarian stimulation. We compared R; 20 mg/day with cetrorelix acetate (C); 0.125 mg. C was administered to 88 women in 2019, and R to 93 women in 2020. Clinical outcomes associated with ART were assessed in both groups. Results The luteinizing hormone levels on the day of human chorionic gonadotropin injection in the R group (1.26 ± 0.93 IU/L) were significantly lower than those in the C group (2.85 ± 3.02 IU/L). There were no cases in which egg retrieval was canceled in both groups. The total doses of gonadotropins administered were greater in the R group compared with the C group. The number of days of GnRH Ant administration in the R group (1.71 ± 0.57 days) was significantly longer compared with the C group (1.48 ± 0.58 days). The number of oocytes collected, fertilization rates, and pregnancy rates (R; 47.1% vs C; 45.8%) did not differ between the two groups. Conclusion An orally active GnRH Ant, relugolix, when used in controlled ovarian stimulation for ART, showed comparable clinical outcomes with cetrorelix.